Consistent measurements of 233U gamma emissions using metallic magnetic calorimeters with ultra-high energy resolution - Kim, Geon-Bo; Kempf, Sebastian; Fleischmann, Andreas; Enss, Christian (Journal of radioanalytical and nuclear chemistry, 2018)
We have used different metallic magnetic calorimeter (MMC) gamma detectors to measure the low-energy emissions of 233U with an accuracy of a few eV. 233U is of interest in nuclear safeguards because it is a fissile isotope that is produced by neutron irradiation of 232Th in the thorium fuel cycle. However, some of the nuclear decay data of 233U in the literature have relatively high uncertainties, especially at lower energies where lines can overlap or be dominated by a high Compton background. MMC gamma detectors operated at a temperature of 10 mK can have an energy resolution below 50 eV and can resolve lines with similar energy and reduce these uncertainties. We present recent MMC measurements of 233U and discuss the contributions of statistical and systematic errors. Importantly, we have performed the experiments with different MMC gamma detectors and different SQUID readout systems to increase the confidence in some observed deviations from literature values. The consistency of the results suggest that observed deviations are not due to detector artifacts and that a predictable quadratic response is intrinsic to the properties of MMCs.
Im Titel ist die Zahl 233 hochgestellt
Gesehen am 18.10.2019